The brain under stress—A systematic review and activation likelihood estimation meta-analysis of changes in BOLD signal associated with acute stress exposure. (May 2021) - Berretz, Gesa; Packheiser, Julian; Kumsta, Robert; Wolf, Oliver T.; Ocklenburg, Sebastian
Highlights: Activation likelihood estimation analysis of stress induction paradigms in the MRI. Overlaying activation patterns in the insula, claustrum, and inferior frontal gyrus. Overlaying deactivation patterns in the parahippocampal gyrus. Systematic review of paradigms identified Cyberball as an outlier. Similar activation patterns between AVP, ScanSTRESS, SET, and MIST. Abstract: Psychosocial stress is an omnipresent phenomenon whose neural correlates in humans are still poorly understood. Several paradigms have been developed to induce acute stress in fMRI settings, but it is unclear whether there is a global brain activation pattern related to psychosocial stress. To integrate the different neuronal activation patterns, we conducted an activation likelihood estimation analysis on 31 studies totaling 1279 participants. Studies used the ScanSTRESS, Montreal Imaging Stress Test, aversive viewing paradigm (AVP), Social-Evaluative Threat or Cyberball. The analysis revealed bilateral activation clusters comprising the claustrum, insula and inferior frontal gyrus. This indicates that exposure to psychosocial stress leads to activations in brain areas involved in affective processing and the endocrine stress response. Furthermore, in a systematic review, Cyberball and AVP presented themselves as outliers due to increased activation in motor areas and lack of induction of stress related activity changes, respectively. As different paradigms emphasize different dimensions of psychosocial stress such as social evaluation or performance pressure, future research is needed to identify differences between the paradigms.